Revealing the Meaning of Gratitude in Qasidah Lisānī Bi Hamdillah by Habib Ali al-Habsyi (Riffaterre’s Semiotic Analysis) - Mubin, A. Faizul; Isra H, Nurul; Hakim, Lukmanul; Anwar, Nirwan (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2024)
تهدف هذه الدراسة إلى استكشاف معاني الشكر في قصيدة